Are You an E-consumer? A Case Study on Finding Factors Impacting Consumers' Purchase Behaviour and Their Willingness to Pay on Average on E-Commerce Platforms in Malaysia - Binti Mohamed Saleh, Nur Syafiqah; Binti Rosli, Nur Syifa`; Binti Halimi, Nur Syafiqah; Binti Badrul Hisham, Nur Syaida Ilyana; Gangurde, Ankita Lahanu (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2023)
Online shopping has become phenomenal in this modern day. Moreover, the world was hit by the enormous Covid-19 pandemic. In the third quarter of 2021, e-commerce platform growth soared up to 17.1% and it also elevated our country’s GDP. People have become more comfortable buying things through the e-commerce platform rather than doing physical buying. These platforms unintentionally affect e-consumer behaviour. This research aims to study consumer behaviour on how much money a person spends on average on e-commerce platforms mainly for online shopping. A total of 150 consumers are surveyed via Google form. We intend to find out if price, customer satisfaction, information quality, and convenience can affect consumers’ purchase behaviour. The result of these findings shows that consumer purchase behaviour is directly related to the price, customer satisfaction with their buying experience and information quality. Consumers are not affected by the convenience variable as deeply as they do by other variables tested in this study. As the study is tested on a survey, the data collected may not be truly accurate.  Keywords: Purchase behaviour, Price, Customer satisfaction, Information quality, Convenience.